(Re)defining the Dichotomies within Moroccan Sufism: Gnawa and Samaã as Case Studies - Qasbi, Qasbi Moulay (Advances in Social Sciences Research Journal, 2021)
Although marked by diversity, the Moroccan Sufi rituals have been associated with mysterious aspects and reputed for the dichotomy of their different facets. The complexity of this field has intrigued my curiosity to investigate to what extent the type of music deployed can contribute to categorizing Sufi orders. In this context, it is worth exploring how the music is used and for which purposes. Through contrasting samaã to gnawa as major Sufi music genres, this paper sheds light on the duality inherent within the former as an elitist Sufi practice and the latter as its popular counterpart. In support if this, I conduct interviews and focus groups with several Moroccan disciples to further investigate the type of audience they both attract and how the two genres help the disciples to get into the Sufi atmosphere and the desired metaphysical level. By reviewing the literature carried out by Moroccan as well as foreign authors in this field, I also look into how researchers position Sufi activities and whether they approach them with awareness of the dichotomies categorizing the two genres within high and low cultures.